DEVELOPMENT AND VALIDATION OF AN INTEGRATED FIRE PREVENTION AND RESPONSE PROTOCOL IN HOSPITALS: A SYSTEMATIC REVIEW - da Silva Borges, Alexander (Health and Society, 2026)
Fire safety in hospitals is a critical component of risk management and patient safety, requiring a systemic and integrated approach. The absence of standardized protocols compromises the safety of critical patients and the continuity of care operations. This systematic literature review aims to synthesize scientific evidence on the development, validation, and implementation of integrated fire prevention and response protocols in hospitals. The analysis covers operational flowcharts, brigade training, critical patient evacuation, and organizational safety culture. Research conducted in databases such as PubMed, SciELO, Scopus, and Web of Science, as well as technical standards repositories, identified that fire response effectiveness depends on the integration of multiple components: clear protocols, competency-based training, realistic simulations, and a robust safety culture. Evidence points to the need for scalable and adaptable protocols that incorporate international best practices and consider different hospital realities. Knowledge gaps include the scarcity of studies in low- and middle-income countries, limited research on complex scenarios with multiple victims, and the need to evaluate long-term effects of training programs. It is concluded that implementing an integrated protocol, validated through simulations and audits, is fundamental to strengthening hospital resilience and reducing the occurrence of serious adverse events related to fires.